MEASURING AND ANALYZING THE PUBLIC INFORMATION DISCLOSURE INDEX: EVIDENCE FROM MAJALENGKA REGENCY - Aceng Jarkasih; Diding Bajuri; Anye Widuri; Dwi Laksmi Ayu Wulandari; Nurul Jannah Lailatul Fitria (ASIAN PUBLISHER, 2024)
Openness of information is demonstrated in information services that minimize disputes over public information and adapt to new media by involving public participation. The implementation of KIP by government agencies needs to be assessed or measured and analyzed based on evidence. Public information disclosure is a fundamental element of transparent, accountable, and participatory governance, particularly in the context of digital transformation and open government. This study aims to measure and analyze the Public Information Disclosure Index (IKIP) in Majalengka Regency and to provide an in-depth explanation of the factors underlying its measurement results. The study employed a mixed- methods approach with a sequential explanatory design, integrating quantitative and qualitative methods in two consecutive stages. The quantitative stage involved 100 respondents, with data collected through structured questionnaires designed to measure the dimensions and indicators of public information disclosure. The quantitative data were analyzed using descriptive statistical analysis and index measurement to determine the level and characteristics of IKIP. Subsequently, qualitative data were collected through interviews and observations to explain, deepen, and validate the quantitative findings. The qualitative data were analyzed through data reduction, data presentation, interpretation, and conclusion drawing. The findings provide an empirical assessment of public information disclosure and identify aspects that support or constrain the quality of information openness in Majalengka Regency. The novelty of this study lies in integrating IKIP measurement with explanatory qualitative analysis, thereby moving beyond numerical index assessment to provide contextual evidence regarding the conditions underlying the resulting scores. This approach contributes to the development of a more comprehensive framework for evaluating public information disclosure and provides practical evidence for local governments to strengthen transparency, accountability, digital information governance, and public participation. The aim is to determine the clear value of IKIP accompanied by evidence-based explanations. The results of the study show that the Public Information Disclosure Index (IKIP) value of 86.3 is in the B quality category, which is good. This is supported by evidence of the Majalengka Regency Government's actions in public information disclosure, which show open governance, new media, and community participation